Comparative Evaluation of In Vitro Activities of Carbapenemes Against Gram-Negative Pathogens: Turkish Data of COMPACT Study - (:unkn) unknown (ANKARA MICROBIOLOGY SOC, 2011)
The aim of this study was to determine the in vitro activities of doripenem, imipenem, and meropenem against clinical gram-negative isolates. A total of 596 clinical isolates were obtained from intensive care unit (ICU) and non-ICU patients in 10 centers over Turkey between September-December 2008. The origin of the isolates was patients with nosocomial pneumonia (42.4%), bloodstream infections (%40.4), and complicated intraabdominal infections (17.1%). Of the isolates, 51.8% were obtained from ICU patients. The study isolates consisted of Pseudomonas spp. in 49.8%, Enterobacteriaceae in 40.3%, and other gram-negative agents in 9.9%. The minimum inhibitory concentrations (MIC) for doripenem, imipenem and meropenem were determined for all isolates in each center using Etest (R) strips (AB Biodisk, Solna, Sweden). Of the isolates, 188 (31.5%) were resistant to at least one of the carbapenems. MIC(50) of doripenem against Pseudomonas spp. was 1 mg/L which was similar to that of meropenem and two-fold lower than imipenem. Susceptibility to carbapenems in P.aeruginosa was 64% for doripenem at an MIC level of 2 mg/L, 53.9% and 63% for imipenem and meropenem at an MIC level of 4 mg/L, respectively. Doripenem and meropenem showed similar activity with the MIC(90) of 0.12 mg/L whereas imipenem was four-fold less active at 0.5 mg/L. Against other gram-negative pathogens, mostly Acinetobacter spp., MIC(50) was 8 mg/L for doripenem and 32 mg/L for other two carbapenems. P.aeruginosa isolates were inhibited 84.2% with doripenem and 72.1% with meropenem at the MIC level of 8 mg/L. Doripenem generally showed similar or slightly better activity than meropenem and better activity than imipenem against pathogens collected in this study. Against Pseudomonas spp., doripenem was the most active of the three carbapenems. Doripenem and meropenem were equally active against Enterobacteriaceae and at least four-fold more active than imipenem. It was concluded that doripenem seemed to be a promising agent in the treatment of nosocomial pneumonia, blood stream infections and intraabdominal infections particularly in patients who were under risk of developing antimicrobial resistance.
Keywords: Carbapenem; doripenem; in vitro activity; gram-negative pathogen; ANTIBIOTIC-RESISTANCE; PSEUDOMONAS-AERUGINOSA; DECLINING SENSITIVITIES; DAUNTING CHALLENGES; DIRE CONSEQUENCES; DORIPENEM; INFECTIONS; MUTANTS; BACILLI